Studi Kepustakaan :Model Pembelajaran Problem Based Learning (PBL) dalam Meningkatkan Keterampilan Membaca pada Mata Pelajaran Bahasa Indonesia di SD - Shintia Dewinta; Elfia Sukma (CV. ITTC INDONESIA, 2026)
This study aims to examine the implementation of the Problem Based Learning (PBL) model in improving students’ reading comprehension skills in Indonesian language subjects at the elementary school level. The method used in this research is a literature study by collecting various sources such as books, scientific articles, and previous research relevant to the topic. The collected data were analyzed using a qualitative descriptive approach to identify patterns, concepts, and findings related to the effectiveness of the PBL model. The results indicate that the PBL model can enhance students’ reading comprehension skills as it encourages critical thinking, active participation, and the ability to connect learning materials with real-life problems. Furthermore, PBL helps students understand texts more deeply through discussion and problem-solving activities